Malondialdehyde levels and glutathione peroxidase activities in the tissues of freshwater crayfish (Astacus leptodactylus esch. 1823) in culture condition - Kandemir, F.M.; Benzer, F.; Erisir, M.; Yildirim, N.C. (My University, 2011)
The objective of the study was to characterize the effects of sex on lipid peroxidation (as malondialdehyde, MDA), antioxidant defence system (as glutathione peroxidase, GSH-Px) in the hepatopancreas, gonad and muscle tissues of freshwater crayfish, Astacus leptodactylus, in culture condition. The crayfish used in the present study was provided from Keban Dam Lake population of A. leptodactylus. 34 males and 30 females crayfish in different size were hold in stock ponds (6 × 6 × 0.5 m). This study was carried out between June 18, 2004 and December 1, 2004 at the crayfish reproduction unit of Aquaculture Faculty of Firat University, Elazig, Turkey. Plastic pipes (20 cm in length and 7 cm in diameter) were provided as shelters for the crayfish. Crayfish were fed 2% of their total wet weight daily with prepared ration. Crayfish were exposed to natural photoperiod. During the study, the mean water temperature, dissolved oxygen and mean pH were 4°C, 6.28±0.32 mg L -1 and 7.82±0.17, respectively. MDA and GSH-Px levels according to sex and tissue-species were determined. MDA level in the hepatopancreas and gonad of females were higher than males, except muscle tissue (P<0.001). However, the GSH-Px activities in the hepatopancreas and gonad of males were higher than females, except muscle tissue (P<0.001). As a result, MDA and GSH-Px levels in the hepatopancreas, gonad and muscle tissues of freshwater crayfish, Astacus leptodactylus, in culture condition changed both tissues and sex.
Keywords: Astacus leptodactylus; Culture condition; Glutathione peroxidase; Malondialdehyde